ANALISIS FAKTOR FUNDAMENTAL SEBAGAI TOLAK UKUR KINERJA KEUANGAN PERUSAHAAN ASURANSI JIWA JOINT VENTURE (Studi Komparasi Perusahaan Peringkat Tinggi dan Perusahaan Peringkat Rendah) - Pratiwi, Yohana Bella; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2015)
Nowadays, financial sector has an important role in Indonesia’s economics growth. It showed by joint venture life insurance company’s growth in Indonesia which have growth rapidly. Purpose of this research is to analyze the effect of loss ratio, expense ratio, combined ratio, and premiums earned to  return on assets of joint venture life insurance company which joined in Asosiasi Asuransi Jiwa Indonesia. This research can also be used to know if there is a significant differences between high rated insurance company and low rated insurance company, and also to know the effect of company rating to insurance company’s return on assets.After doing a literature review, we can obtain secondary data from 15 financial reports of joint venture life insurance company and also best insurance rank from Infobank Daily. The data are analyzed by classical assumption test, regression analysis with dummy variabel test, and chow testThe result of this study shows that loss ratio has negative and no significant effect, expense ratio and combined ratio have positive and no significant effect, and premiums earned has positive and significant effect to return on assets. The result also shows there is no significant differences between high rated insurance company and low rated insurance company. High rated insurance company’s return on assets is 20,7% higher than low rated insurance company’s return on assets.